2017
DOI: 10.1371/journal.pone.0178729
|View full text |Cite
|
Sign up to set email alerts
|

ADAMTS-1 in abdominal aortic aneurysm

Abstract: IntroductionExtracellular matrix degradation is a hallmark of abdominal aortic aneurysm (AAA). Among proteases that are capable of degrading extracellular matrix are a disintegrin and metalloproteases with thrombospondin motifs (ADAMTS). Pathogenesis of these proteases in AAA has not been investigated until date.Methods and resultsHuman aneurysmal and control aortas were collected and analyzed with RT-PCR measuring the ADAMTS-1, 4,5,6,8,9,10,13,17 and ADAMTSL-1. Expression of a majority of the investigated ADA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 16 publications
2
19
0
1
Order By: Relevance
“… 53 , 54 Mice lacking THBS1 exhibit reduced AAA severity in different experimental models of AAA. 34 , 54 THBS1 can be proteolytically processed by ADAMTS1 38 ; however, ADAMTS1 does not appear to be an important player in AAA, 41 and we found it to be decreased in the AAA tissues as also reported by others. 41 We found that Ang II upregulates THBS1, as also reported by others, 55 , 56 as well as ADAM15.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“… 53 , 54 Mice lacking THBS1 exhibit reduced AAA severity in different experimental models of AAA. 34 , 54 THBS1 can be proteolytically processed by ADAMTS1 38 ; however, ADAMTS1 does not appear to be an important player in AAA, 41 and we found it to be decreased in the AAA tissues as also reported by others. 41 We found that Ang II upregulates THBS1, as also reported by others, 55 , 56 as well as ADAM15.…”
Section: Discussionsupporting
confidence: 84%
“… 34 , 54 THBS1 can be proteolytically processed by ADAMTS1 38 ; however, ADAMTS1 does not appear to be an important player in AAA, 41 and we found it to be decreased in the AAA tissues as also reported by others. 41 We found that Ang II upregulates THBS1, as also reported by others, 55 , 56 as well as ADAM15. ADAM15 could proteolytically process THBS1 or bind to THBS1, preventing it from activating its receptors, and as such, the absence of ADAM15 will result in highly elevated THBS1 levels.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Notably, the degradation of versican by ADAMTS1 has been revealed to contribute to atherosclerosis (33). A recent study conducted by Vorkapic et al (34) has also demonstrated the association between the cleavage of ADAMTS1 substrates and atherosclerosis development. Furthermore, in an acute aortic dissection (AAD) mouse model, it was suggested that ADAMTS1 promotes the progression of AAD by degrading versican in macrophages and neutrophils (35).…”
Section: Discussionmentioning
confidence: 96%
“…Biopsies were fixed in 4% formaldehyde for immunohistological analyses, snap-frozen in liquid nitrogen for protein analysis, or placed in RNAlater (Ambion, Austin, TX, USA) overnight at 4°C, and then stored at −80°C for RNA isolation as described previously [24]. Tissue samples were from non-AAAs and AAAs (aortic diameter >55 mm from computed tomography scan).…”
Section: Methodsmentioning
confidence: 99%